(untitled) (ARQUISUR Revista, 2019)
The European Landscape Convention is an international treaty that is specifically and exclusively dedicated to European landscapes, although the issues it raises are of general interest. This Convention, unlike other previous normative texts, proposes a series of novelties. Among them, the one that is most important is the definition that it makes of the concept of landscape and the consequences of this conceptualization for a landscape policy. For the first time, we find a treaty that focuses not only on those natural or rural areas, but also urban and peri-urban. In the development of this article, we intend to investigate what this Convention has meant for peri-urban landscapes and what is the current state of implementation of its principles, strategies and guidelines. For this, we will focus on its analysis, as well as on the study of the most relevant scientific literature related to its study and implementation. All this will allow us to take stock of its development and application in the peri-urban environment, in the end, to define a series of actions aimed at covering the deficiencies detected in its implementation and to pose future challenges for these landscapes.